THE EFFECT OF SURFACTANTS ON SUPERCONFORMAL DEPOSITION OF ELECTROLESS COMPOSITES IN NANOSCALE PATTERNS - V. A. Bogush (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Electroless plating of metal composites has been proposed as a promising method for metallization of high aspect ratio trenches for micro- and nanoelectronics and microelectromechanical systems application. Deposition of Ag(W) electroless films was performed from ammoniate silver solution to fill deep damascene trenches. Polyethylene glycol (PEG) with molecular weight of 400, 1500 and 6000, RE-610 and Triton X-100 were studied as an additives in the plating bath for superconformal deposition. The deposition rate, resistivity, grain size and the trench filling behaviour were studied as a function of the additives concentration and deposition temperature using Scanning Electron Microscopy (SEM) cross section study. The PEG with molecular mass about 1500 was found to provide superconformal Ag(W) electroless growth in nanometre wide trenches.